Integrated Transportation – Inventory Model for Outbound Logistics Optimization Hajariyah Agustina and Budi Santosa Departemen of Management Technology, Institut Teknologi Sepuluh Nopember (ITS), Surabaya e-mail: hajariyah.agustina@gmail.com of Cement - Agustina, Hajariyah; Santosa, Budi (IPTEK Journal of Proceedings Series, 2020)
In the cement industry, supply chain management has an important role in determining competitiveness from inbound logistics to outbound logistics. PT X is the largest cement company in Indonesia with market share about 53% in 2019. The Company’s key strategy is supply chain optimization to achieve logistics and transportation cost efficiency and also prioritizing service level to meet customer needs. Outbound logistics optimization in PT X can be approached with the Integrated Transportation-Inventory (ITI) model. ITI is a model that integrates transportation and inventory decisions. In addition, ITI can also determine inventory levels, production quantities and backorder decisions. The application of ITI at PT X case study is categorized as multiple to multiple supply chain configurations, transshipment, multi-period, multi-product, allowing for back orders, and deterministic demand. The results of simulations of ITI models can be used as a basis sales planning and production. In this research, the ITI model solved with simplex solver method on Lingo 18, which has features to improve computational processes of a large scale cases. The development of the ITI model in optimizing outbound logistics at PT X provides efficiency and effectiveness of distribution strategy to meet customer demand. Simulation results show that optimization of outbound logistics using the ITI model is able to save costs by 1.86% (worth 117 billion) compared to existing conditions.